PENGARUH MINAT BELAJAR DAN PERSEPSI SISWA TENTANG PENGELOLAAN KELAS OLEH GURU TERHADAP HASIL BELAJAR SISWA KELAS XI IPS PADA MATA PELAJARAN EKONOMI DI SMA NEGERI 15 PADANG - Fitriani, Fitriani; Armiati, Armiati; Afriza, Rina (Pendidikan Ekonomi, 2014)
ABSTRACTThis study aims to analyze : 1 ) the influence of student interest on learning outcomes of students in class XI in the subjects of Economics in SMAN 15 Padang, 2 ) students perceptions about classroom management by teachers on student learning outcomes in class XI in the subjects of Economics in SMA 15 Padang 3 ) the influence of student interest and student perceptions of classroom management by the teacher to the student learning outcomes in class XI in the subjects of Economics at SMA Negeri 15 Padang.When the study was conducted in January 2014. Research used in this study is a descriptive study associative. The study population was all students of class X SMA Negeri 15 Padang numbered 142 people. Sampling technique with proportional random sampling with a sample size of 104 people. Data analysis techniques : descriptive analysis and inductive analysis, namely normality test, heteroscedasticit, multikoleniaritas test, autocorrelation test and multiple regression analysis with SPSS version 16.0. The results showed that : there is a significant and positive influence students interest on learning outcomes of students in class XI in the subjects of Economics (sig = 0.000) with the degree of influence (0.170), there is a significant and positive impact on students perceptions of classroom management by the teacher to class XI student learning outcomes in the subjects of Economics (sig = 0.001) with the degree of influence (0.068), which means that there are significant and positive influence student interest and students perceptions about classroom management by teachers together on learning outcomes of students of class XI IPS in the subjects of Economics in SMAN 15 Champaign school year 2013/2014 (sig = 0.000) with a contribution rate of 60.8%.Based on the research results, it is expected that students and teachers can interact in a balanced way so as not to stiff and tense during the learning process is expected to take place as well as teachers can manage the class well and always pay attention to the teacher, keep the attitude at the time of the learning process takes place so as to create the circumstances conducive to the learning process can proceed smoothly and peacefully, and students are expected to not give up and do not easily get bored to learn the teachers economy.